Attack on Titan. Before the fall, 8 - Isayama, Hajime, 1986-; Suzukaze, Ryo (Kodansha Comics, 2016)
Kuklo heads to Shiganshina District to test the new model of the Device, while Sharle anxiously awaits his return at Xenophon's workshop. But long after Kuklo's expected date of return, there is still no sign of him. Meanwhile, an anti-government group carries out a plan in the Industrial City, where Sharle works. Little do they know, Xavi has infiltrated the mission on orders from above.